Pathway into translation online teaching and learning: three case-studies - Valentine, Egan; Wong, Janice (The Journal of Specialised Translation, 2021)
Promoting effective student engagement and learning in the online environment continues to challenge translation instructors. This article shares findings from three case studies conducted over a ten-year period at the University of Quebec in Trois-Rivières, Canada. The underlying concern was to generate meaningful interaction and student engagement in online translation instruction. Initially the discussion board was found to be instrumental for punctual questions, knowledge sharing and course logistics. With larger groups, however, it proved tedious and less effective for promoting higher order thinking for translation problem solving. Incorporating collaborative tasks, using videoconferencing technology enabled the instructor to promote and observe active student interaction and identify obstacles to learning. Two obstacles spring to light: students need guidance for conducting effective teamwork and discussing translation solutions objectively. Providing instructions on teamwork and a framework for approaching translation problems is essential. Further work is envisaged to promote higher order thinking by emphasising metacognitive awareness as students learn by themselves and with others.